Raspberry pi 2: beginners guide - Scott, Robert; Scott, Robert ([United States?] : CreateSpace Independent Publishing Platform, 2015)
Amazon #1 Best Seller - Download it Now! It functions like any normal computer. You can plug this into any television or computer monitor and operate it with your normal keyboards. You can surf through various internet sites, watch HD videos, or indulge in some games. What is this amazing device that I have just described? It is none other than Raspberry pi 2! If you are computer geek like me, you probably heard of the release of raspberry pi 2, this release will definitely change the entire game of modern electronic projects! However with the complexity that Raspberry pi 2 has, people are too afraid to get started. No worries, with this book I've got you covered!
Introduction -- Chapter 1. Basic Description of Raspberry Pi 2 -- Chapter 2. Test the Demo Programs of Raspberry Pi 2 -- Chapter 3. Write your first Program with Astro Pi -- Chapter 4. Set up noobs for Raspberry Pi 2 -- Chapter 5. Build your home theater using Raspberry Pi 2 -- Chapter 6. Operating system for Raspberry Pi 2 -- Chapter 7. Languages used with Raspberry Pi 2 -- Chapter 8. Creating games and music box with Raspberry Pi 2 -- Chapter 9. Use Raspberry Pi 2 tips and tricks -- Conclusion -- Other recommendations.
Keywords: RASPBERRY PI (COMPUTER) -- POPULAR WORKS